2010
DOI: 10.15288/jsad.2010.71.810
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Alcohol Dependence in Young Women

Abstract: ABSTRACT. Objective:The aim of the current study is to characterize the relationship between posttraumatic stress disorder (PTSD) and alcohol dependence (AD) in women, distinguishing PTSD-specifi c infl uences on AD from the contribution of co-occurring psychiatric conditions and from the infl uences of trauma more generally. Method: Trauma histories and DSM-IV lifetime diagnoses, including PTSD and AD, were obtained via telephone interview from 3,768 female twins. Based on PTSD status and trauma history, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 60 publications
(104 reference statements)
3
33
0
1
Order By: Relevance
“…Taken together, these results support partial mediation of IPV-problem drinking relationship by MDD, suggesting that other indirect paths may exist independent of MDD. This fi nding is consistent with prior studies suggesting that psychiatric conditions at least partly account for the relationship between prior trauma and alcohol use (Edwards et al, 2006;Sartor et al, 2010). The current study's results should be considered with longitudinal research by Fergusson and colleagues, which suggests the causal direction fl ows from AUD to MDD (Fergusson et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, these results support partial mediation of IPV-problem drinking relationship by MDD, suggesting that other indirect paths may exist independent of MDD. This fi nding is consistent with prior studies suggesting that psychiatric conditions at least partly account for the relationship between prior trauma and alcohol use (Edwards et al, 2006;Sartor et al, 2010). The current study's results should be considered with longitudinal research by Fergusson and colleagues, which suggests the causal direction fl ows from AUD to MDD (Fergusson et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Humans with stress-related anxiety disorders (e.g., post-traumatic stress disorder [PTSD]), exhibit increases in arousal and alcohol drinking, as well as altered pain processing (Engdahl et al, 1998; Norrholm et al, 2011; Roy et al, 2012; Sartor et al, 2010). In animals, a single intense stress or chronic stress produces hyperalgesia (Boccalon et al, 2006; da Silva Torres et al, 2003; Geerse et al, 2006; Quintero et al, 2000; Zhang et al, 2012), increases anxiety-like behaviour, and produces hyperarousal in rats (Campos et al, 2013; Kinn Rød et al, 2012; Serova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal study, Clark and colleagues (2003) found that a history of physical or sexual abuse in adolescents and young adults did predict primary major depressive disorder and alcohol use disorder later in life. Similarly, Sartor et al (2010) found that women exposed to trauma had higher rates of alcohol dependence whether or not they met the criteria for PTSD. In their cross-sectional study, Sartor et al (2010) also found that women with PTSD had higher rates of major depressive disorder.…”
Section: Common Factor Modelmentioning
confidence: 92%
“…Similarly, Sartor et al (2010) found that women exposed to trauma had higher rates of alcohol dependence whether or not they met the criteria for PTSD. In their cross-sectional study, Sartor et al (2010) also found that women with PTSD had higher rates of major depressive disorder.…”
Section: Common Factor Modelmentioning
confidence: 92%